Hearing health survey of the population in Bangkok - Suwimol Ruencharoen; Krisna Lertsukprasert; Ravin Suvanich; Jirapat Seesangnom; Mondnath Chockboondee; Wichai Aekplakorn; Chanchai Jariengprasert; Sivaporn Kiatthanabumrung; Tosapohn Wisupagan (BMC, 2024)
Abstract In this cross-sectional random survey among Thai adults living in Bangkok, we aimed to identify the prevalence of hearing problems and examine their relationship with individual factors. We administered a self-report questionnaire and performed pure-tone air conduction threshold audiometry. A total of 2463 participants (1728 female individuals) aged 15-96 years were included. The hearing loss prevalence was 53.02% and increased with age. The prevalence of a moderate or greater degree of hearing impairment was 2.8%. Participants aged 65 years and over had 8.56 and 6.79 times greater hearing loss and hearing impairment than younger participants, respectively. Male participants were twice as likely to have hearing loss and hearing impairment as female individuals. Participants with higher education levels showed less likelihood of having hearing loss and hearing impairment than those with no or a primary school education. Participants who ever worked under conditions with loud noise for > 8 h per day had 1.56 times greater hearing loss than those without such exposure. An inconsistent correlation was found between hearing loss, hearing impairment and noncommunicable diseases (diabetes, hypertension, and obesity). Although most participants had mild hearing loss, appropriate care and monitoring are necessary to prevent further loss in such individuals. The questionnaire-based survey found only people with hearing problems that affect daily communication.